Evolution of temperature regime of plastic deformation mantle peridotites; Siberian Early Career GeoScientists Conference - Chernyshov A. I. Aleksandr Ivanovich (Petrology and geochemistry of igneous and metamorphic rocks, 2016)
Title screen